Regional disparities in the flow of access to breast cancer hospitalizations in Brazil in 2004 and 2014 - Beatriz Castro de Souza; Francisco Winter dos Santos Figueiredo; Luiz Vinicius de Alcantara Sousa; Erika da Silva Maciel; Fernando Adami (BMC, 2020)
Abstract Background Access to the diagnosis and treatment of breast cancer in Brazil is marked by immense inequalities in the provision of specialized assistance, which leads patients to seek treatment outside the place of residence. To evaluate the variations between 2004 and 2014 in the distribution of flow between place of residence and care, and the average distance traveled for treatment of breast cancer in the administrative regions and federal states of Brazil. Method Analysis of secondary data from the years 2004 and 2014, extracted from the Department of Informatics of the Unified Health System through the Hospital Information System. Data from Hospitalization Release Authorizations were collected, and the maps were created with TabWin 3.6 software. Descriptive analysis was performed on Stata® (StataCorp, LC) 11.0. Results In the total flow, it was observed that there was a decrease in referrals between 2004 and 2014 in most regions. In 2004 the main direction of flow was in the Midwest and Southeast regions. In 2014, however, the intensity of these admissions was centralized in the Southeast region. In relation to the average distance traveled, the North, Northeast, and Midwest regions had the highest values of displacement. Of the 27 federative units, 17 presented an increase in average distance between these periods. Conclusion Despite the improvement in the hospitalization of residents, in most regions and federal units, Brazilians still travel great distances when they require treatment for breast cancer.